The role of universities and other institutions in successful entrepreneurship: Some insights from a literature review - Zarate Hoyos, Germán A. (2015)
The purpose of this paper is to analyze the role of universities and other institutions in successful entrepreneurship. Insights are obtained following a literature review approach. Case studies from the United States (New York startup), Spain (Mondragon), and Germany provide strong evidence that universities are very instrumental in the creation, design and implementation of entrepreneurial initiatives by providing new and ongoing entrepreneurs with human capital training, fundamentals, and theoretical and empirical models to contribute to lasting businesses. Results from university research on gender and risk-issues lead to believe that women are more risk averse than men to work and invest in star-up businesses. Other institutions, such as governments, are critical to provide with the necessary incentives to launch start-up businesses, including tax cuts, seed capital funding, investment in human capital, etc. While the evidence supporting the links between education and entrepreneurial outcomes is promisi g it is not yet definitive. In addition to providing a review of existing research, this paper suggests an integrative framework for future research.